Relationship between occlusal vertical dimension and linear ear length - Elizabeth Julcamoro Grados; Felipe Lozano Castro; Yuri Alejandro Castro Rodríguez (Editorial Ciencias Médicas, 2020)
Introduction: When occlusal vertical dimension becomes altered, as is sometimes the case, use should be made of subjective and objective methods, including those based on an anthropometric approach. Objective: Evaluate the correlation between linear ear length and vertical dimension in dentate young subjects. Methods: A total 47 students were evaluated for linear vertical ear length (from the highest to the lowest end of the earlobe), and measurements were taken from the outer edge of the ocular hole to the tragus and the vertical occlusal dimension (located at the subnasal point and the most prominent edge of the chin). All measurements were taken with a digital caliper. Results: Average vertical occlusal dimension was 65.68 ± 4.14 mm. Average distance from the outer edge of the eye to the right tragus was 67 ± 3.52 mm (r correlation = 0.776; p < 0.01), whereas on the left side it was 66.95 ± 3.98 mm (r correlation = 0.733; p < 0.01). Ear length distance was 64.74 ± 4.47 mm on the right side (r correlation = 0.643; p < 0.01) and 64.84 ± 4.46 mm on the left side (r correlation = 0.657; p < 0.01). Conclusions: Right and left linear ear length anthropometric measurements correlated with vertical occlusal dimension. The distance from the outer edge of the eye to the tragus also correlated with the vertical occlusal dimension.